Designing Teaching Materials Based on Students Book to Improve Students Reading Skill in the Merdeka Curriculum - Rusmaladewi, Ni Kadek Dian; Dewi, Ni Putu Artila; Suryantini, Made Detri (Riwayat: Educational Journal of History and Humanities, 2025)
This research aimed at (i) designing effective teaching materials based on students book to support the Merdeka Curriculum; (ii) assessing the validity level of the designed teaching materials; and (iii) determining the effectiveness of the materials in improving third-grade students reading skill. This research employed a combination of qualitative and quantitative methods. The ADDIE model was employed, focusing on the analysis, design, development, and implementation stages. The research subjects were 21 third-grade students of SDN 1 Tamanbali. Data were collected through observation, interviews, questionnaires, and pre-test and post-test instruments. The qualitative data were analyzed using coding and thematic analysis, while the quantitative data were analyzed using descriptive statistics and the Wilcoxon test. The results showed that the existing student book lacked sufficient content and engagement to support reading skill development. Based on the needs analysis, the researcher developed teaching materials entitled My First English Reading Journey, Consisting of three units with reading texts, vocabulary, illustrations, and comprehension tasks. Expert validation confirmed the materials were valid in terms of content, language, and media design. Implementation of the materials led to a significant improvement in students reading skills, as indicated by increased post-test scores and positive feedback from students and the teacher. It was concluded that well-designed student book-based teaching materials can effectively enhance reading skills and support the implementation of the Merdeka Curriculum in primary schools.